The implications of COVID-19 for concepts and practices of citizenship. (1st January 2022) - Moon, M. Jae; Cho, B. Shine
Abstract : Based on a review of citizenship and citizen participation in politics and policy studies, this article reveals diverse concepts of citizens and citizenship and their changing roles within the context of the COVID-19 pandemic. It argues that the pandemic will result in bringing citizens back into the policy process, given that active participation of citizens in solving wicked social problems has been emphasised. Our results suggest that the pandemic will result in a return of public citizens as their voluntary, active participation and coproduction practices are expected to increase.